2004
DOI: 10.1520/jai11355
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Neutron Flux on Radiation-Induced Embrittlement in Reactor Pressure Vessel Steels

Abstract: The effect of neutron flux level is a longstanding concern for determining the applicability of test reactor data or high lead-factor surveillance data to the prediction of embrittlement in commercial reactor pressure vessels (RPV). However, as operating reactors reach higher fluences, the question of flux effects is becoming increasingly relevant for situations such as embrittlement attenuation through the (RPV) and the comparison of boiling and pressurized reactor RPVs. In spite of its technological importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…A similar result was found for the precipitates in a low copper steel from the Chooz reactor [41]. The size of Cu-enriched precipitates increases under irradiation [42][43][44].…”
Section: Resultssupporting
confidence: 78%
“…A similar result was found for the precipitates in a low copper steel from the Chooz reactor [41]. The size of Cu-enriched precipitates increases under irradiation [42][43][44].…”
Section: Resultssupporting
confidence: 78%
“…Recall that the JFL samples contained 0.01% Cu (low-copper steel), and the JRQ samples contained 0.14% Cu (medium-copper steel). It has been shown that the dominating hardening mechanism in low-copper steels are other defects such as point defect clusters and manganesenickel precipitates [13,19]. It is plausible that these defects, as well as UMDs as suggested in [13], have formed in the high fluence samples of the low-Cu JFL material, creating more pinning points for dislocations and thus causing a decrease in β, which would align with the experimental results.…”
Section: Effects Of Neutron Flux and Compositionsupporting
confidence: 77%
“…The effect of higher fluxes typical of test reactors depends on the combination of copper content, irradiation temperature, and neutron fluence [13,19]. It has been shown that in low Cu steels, higher flux typical of test reactors can produce increased hardening at higher fluence due to an increased amount of unstable matrix defects (UMDs) [13].…”
Section: Effects Of Neutron Flux and Compositionmentioning
confidence: 99%
“…Rate theory is one method of computational simulation that can address this issue and develop radiation-induced hardening models. Neutron flux and dose levels in the operational range (low to intermediate) are of particular concern, and data is not well determined [60]. Thus, illustrating the radiation effects becomes increasingly difficult.…”
Section: Displacement Damage Rate Dose Rate Flux Andmentioning
confidence: 99%
“…− 10 !!! / ) [60]. Typical surveillance experiments for embrittlement often result in 3-5 times greater flux than the maximum observed RPV flux; similarly material sensitivity to radiation is generally analyzed at 10 to 1000 times greater flux [60].…”
Section: Displacement Damage Rate Dose Rate Flux Andmentioning
confidence: 99%